Dampak Inovasi Layanan Pembayaran Pajak Restoran Secara Online Melalui Aplikasi “Si Panjol Mobile” Terhadap Kepatuhan Wajib Pajak di Kabupaten Mojokerto - Mahardika Dimas Saputra; Theofila Chevara Aira Nazaputri; Rahma Farahdini Putri; Addin Thathit Yudha Kusuma; Agus Widiyarta (Public Service and Governance Journal, 2025)
This study examines the impact of the SiPanjol Mobile application on tax compliance among trestaurant taxpayers in Mojokerto Regency. The digital tax payment service helps address common issues in manual systems, such as delayed reporting and lack of transparency. Using a qualitative descriptive approach, data were gathered through interviews and field observations. The findings indicate that the application simplifies reporting and payment processes while promoting voluntary compliance. Overall, SiPanjol Mobile contributes to a more accessible and transparent local tax system.